Power and Gender: Female Perspective - Khamseh, Zahra (2009)
In this research through pilot study, I seek and explore the cultural differences of Iranian and Malay females by illustrating their stories. I believe that in organizational studies, stories are valuable constructs; therefore, I adopt storytelling approach to capture the lovely moments, through living among individuals. In addition, by adopting narrative approach in this research, along with my ethnography position, I am able to write about my Iranian friends and Malay classmates’ stories very contentedly. In this research, I attempt to find out the role of culture in relation with female issues specially “women representation on boards, and in senior management role” and “Empowering women towards greater equality” (Women Summit, 2009). Therefore, my characters [interviewees] told their stories about their family, society and organization; through their stories I managed to find that Iranian and Malay females though might have the same fundamental similarities, they are culturally different. Thus, I adopt Hofstede’s (1980, 2005) cultural dimensions to find the similarities and differences of both groups. As above mentioned issues have their roots in culture – Power Distance Index [Hierarchy], and Masculinity- as a result, in this research, I have to focus only on PDI and MAS. I explore the effect of unwritten rules and regulations; I view and analyze individual’s decision which is influenced by Family, Society and Organization. I find what I believe, the strong effects of unwritten rules and regulations which bind family members, people in one organization, and society as a whole together by the “basic assumption” (Schein,1985, 2004). People attempt to transfer all these unwritten rules and regulations – culture – from one generation to next generation. Hence, culture embeds in an individual, family, society and in an organization, as organizational culture. It cannot be separated from organization, although it is hard to see due its invisible characteristic; its enormous effect on company’s performance, company’s success, company’s core competencies, and company’s competitive advantage is incredible, as Japanese and Korean cultures have contributed to their countries success stories.